2008
DOI: 10.1007/s11904-008-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations associated with HIV infection

Abstract: Oral lesions are among the early signs of HIV infection and can predict progression to AIDS. The lesions commonly associated with the infection include oral candidiasis, herpes simplex infection, oral Kaposi's sarcoma, oral hairy leukoplakia, parotid gland enlargement, gingival diseases, xerostomia, and recurrent oral ulcerations. The introduction of highly active antiretroviral therapy has changed the epidemiology of some of the oral diseases associated with HIV infection. This review discusses the oral manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 65 publications
1
50
1
5
Order By: Relevance
“…In fact, a high prevalence of oral bacterial (e.g., HIV-1 gingivitis and periodontitis), fungal (e.g., pseudomembranous candidiasis), and viral (e.g., oral hairy leukoplakia and Kaposi's sarcoma) coinfections in HIV-1 ϩ patients has been described widely (18,55). Evidence also suggests that periodontal disease, oral candidiasis, and oral hairy leukoplakia positively correlate with higher HIV viral loads (1,2,15,28,59), although the potential for oral pathogens to stimulate latently infected cells and induce HIV-1 reactivation has received little attention (27).…”
mentioning
confidence: 99%
“…In fact, a high prevalence of oral bacterial (e.g., HIV-1 gingivitis and periodontitis), fungal (e.g., pseudomembranous candidiasis), and viral (e.g., oral hairy leukoplakia and Kaposi's sarcoma) coinfections in HIV-1 ϩ patients has been described widely (18,55). Evidence also suggests that periodontal disease, oral candidiasis, and oral hairy leukoplakia positively correlate with higher HIV viral loads (1,2,15,28,59), although the potential for oral pathogens to stimulate latently infected cells and induce HIV-1 reactivation has received little attention (27).…”
mentioning
confidence: 99%
“…Since the first report in 1984, OHL has been observed mainly in AIDS patients 4,[22][23][24] . However, OHL has been reported in other immunosuppressed patients, including those with ulcerative colitis, pemphigus vulgaris, bullous pemphigoid, Behcet's syndrome, multiple myeloma, and leukemia 5,6,16,17,25 .…”
Section: Discussionmentioning
confidence: 99%
“…WHO proposed the immunological classification on the basis of CD4 count as none or not significant -Group 1 (>500/ ml), mild -Group 2 (350-499/ml), advanced -Group 3 (200-349/ml) and severe -Group 4 (<200/ml). Studying the prevalence of AIDS-related oral lesions in different regions of the world is important as it provides a more thorough description of the epidemic and scientific basis for the appropriate management of the disease by health care workers [8]. Although some lesions such as candidiasis and hairy leukoplakia are considered as prognostic factor of HIV disease, recent data have indicated that concurrent existence of multiple and variable oral lesions is accompanied with poor prognosis of the disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the patients with oral candidiasis were suffering from severe immunosuppression, and they concluded that candidiasis and gingivitis could be considered as an indicator of the disease progression [4]. The research work conducted by Sud et al and Nokta have also shown an association between low CD4 counts and candidiasis, linear gingival erythema, angular cheilitis, scabies, paronychia, oral pigmentation, diffuse hair loss and other oral symptoms [7,8].…”
Section: Introductionmentioning
confidence: 99%